"We don't snack": Attitudes and perceptions about eating in-between meals amongst caregivers of young children. (1st January 2017) - Jacquier, Emma F.; Gatrell, Anthony; Bingley, Amanda
Abstract: Objective: Little is known about caregiver attitudes and perceptions towards snacking by toddlers and preschool children outside of the U.S. This qualitative study examined caregiver attitudes and perceptions towards the provision of both foods and beverages in-between meals, along with what constitutes a snack, or snacking occasion, amongst Swiss caregivers. Study design, setting and participants: This qualitative study used in-depth interviews (n = 17) conducted with caregivers (16 = female, 3 = male, ages = 20-46y, low to high income). The "Food Choice Process Model" was used as a theoretical framework. Interviews explored experiences, attitudes and perceptions about the provision of foods and beverages to children (1-5y) in-between meals. Interview transcripts underwent a thematic analysis and key themes were developed from the data. Results: Five key themes were identified; 1) Timing is everything 2) Location + food type = snacking 3) Snacks are junk 4) Snacks are small 5) Not in front of the children. The clock-time at which young children were fed, the location, the food type and the portion size delineated how caregivers conceptualised snacking. Feeding children at 10am and 4pm was not viewed as snacking, nor was providing milk before bedtime. Conclusions and Implications: Eating in-between meals and snacking may be perceived by caregivers as different concepts and vary according to geography, contexts, time of day, food type and location. The findings highlight some agreement with similar studies conducted in the U.S. but also provide new insights into how the consumption of foods and beverages in-between meals may vary between geographic settings. The opportunities for better defining "snacking" within nutrition study design, and how this may inform dietary intake data interpretation, are discussed.